The nexus of culture value, self-efficacy, and personal branding: A mediated approach - Lumbantobing, Rebekka Artauli; Yohana, Corry; Saptono, Saptono (Edelweiss Applied Science and Technology, 2024)
The purpose of this study is to obtain a new concept about the influence of cultural value on personal branding with self-efficacy mediation. This type of research is quantitative with a positivism paradigm and compiles research hypotheses related to the variables of artistic value, self-efficacy, and personal branding. The population of the study was members of the National Police Personnel at the Central Kalimantan Regional Police, totaling 1,440 personnel. The sampling technique used a sampling frame so that 303 samples were obtained. The results of the study indicate that there is a direct positive and significant influence of cultural value on personal branding because cultural value is a moral foundation that is internalized in professional life and self-efficacy increases self-confidence and accuracy in carrying out tasks. The novelty of the study, integrating self-efficacy as a mediating factor between cultural value in forming personal branding of National Police members by developing scientific insights into the Theory of Organization Behavior (TOB) and Theory of Planned Behavior (TPB) into the development of scientific self-management-personal branding to obtain a new model of self-management-personal branding for National Police personnel. Future research by integrate career development in the development of soft skills and hard skills that support personal branding and develop the internalization of cultural values through socialization and role-modeling.